2014
DOI: 10.2135/cropsci2013.06.0363
|View full text |Cite
|
Sign up to set email alerts
|

Planting Pattern and Irrigation Effects on Water‐Use Efficiency of Winter Wheat

Abstract: The world food demand is expected to double by 2050 and the availability and quality of irrigation water is declining because of the needs of the expanding population combined with the effects of climatic change. Therefore, productivity and water‐use efficiency (WUE) are crucial issues in the production of winter wheat (Triticum aestivum L.). The objective of this field study was to compare and evaluate the soil water characteristic, evapotranspiration (ET), yield, and yield components to identify possible way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The highest total dry matter yield (mean for two years) of 9257.9 kg ha −1 was gained from intercropping of berseem clover + 50% basil with surfactant application, supported by a report from Wang et al (2014). The results indicate that interaction between planting pattern and surfactant application has a significant effect on yield (Fig.…”
Section: Effect Of Irrigation Treatments and Surfactant On Total Dry supporting
confidence: 68%
“…The highest total dry matter yield (mean for two years) of 9257.9 kg ha −1 was gained from intercropping of berseem clover + 50% basil with surfactant application, supported by a report from Wang et al (2014). The results indicate that interaction between planting pattern and surfactant application has a significant effect on yield (Fig.…”
Section: Effect Of Irrigation Treatments and Surfactant On Total Dry supporting
confidence: 68%
“…The furrow-ridge seedbed planting pattern resulted in higher winter wheat yield, grains/spike and thousand grain weight when irrigated at 135 or 180 mm rather than the 90 mm irrigation treatment, and there were no significant differences between yield, spikes/m 2 , grains/spike and thousand grain weight of 135 mm with those of 180 mm irrigation treatment in 2009/ 10. However, the irrigation level of 135 mm resulted in a larger increase in yield than the 180 mm irrigation treatment (Wang et al 2014). Furthermore, leaf water use efficiency of the 135 mm irrigation treatment was greater than that of the 180 mm irrigation treatment.…”
Section: Discussionmentioning
confidence: 83%
“…The wheat yield was significantly positively correlated with soil water content, stomatal conductance, leaf relative water content, leaf water potential, grains/spike and thousand grain weight, which corresponded with the results of Wang et al . (2014). The furrow–ridge seedbed planting pattern resulted in higher winter wheat yield, grains/spike and thousand grain weight when irrigated at 135 or 180 mm rather than the 90 mm irrigation treatment, and there were no significant differences between yield, spikes/m 2 , grains/spike and thousand grain weight of 135 mm with those of 180 mm irrigation treatment in 2009/10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the presence of the wheat residue increased rainfall-use efficiency by 50% because of the reduced soil water evaporation. Wang et al (2014) evaluated planting pattern and irrigation on wheat in the North China Plain and found a combination of furrow ridge planting combined with 135 mm of irrigation increased WUE by nearly 14% and suggested that this strategy would provide a more efficient production system in water-limited environments. Ibrahim et al (2015) showed that mulching and micro-dosing of NPK fertilizer increases WUE in low-input agriculture in a semi-arid climate.…”
Section: Cultural Practices At the Canopy Scalementioning
confidence: 99%